Factors affecting the overcrowding in outpatient healthcare - Bahadori, Mohammadkarim (J Educ Health Promot, 2017)
BACKGROUND: The expansion of outpatient services and the desire to provide more outpatient care than inpatient care create some problems such as the overcrowding in the outpatient clinics. Given the importance of overcrowding in the outpatient clinics, this qualitative study aimed to determine the factors influencing the overcrowding in the specialty and subspecialty clinic of a teaching hospital. MATERIALS AND METHODS: This was a qualitative study conducted in the specialty and subspecialty clinic of a hospital using content analysis method in the period of January to March 2014. The study population was all managers and heads of the outpatient wards. The studied sample consisted of 22 managers of the clinic wards who were selected using the purposive sampling method. The required data was collected using semi-structured interviews. The collected data was analyzed using conventional content analysis and the MAXQDA 10.0 software. RESULTS: Three themes were identified as the main factors affecting the overcrowding including the internal positive factors, internal negative factors, and external factors. CONCLUSIONS: Despite the efforts made to eliminate overcrowding, and reduce waiting times and increase access to the services for patients, the problem of overcrowding still has remained unresolved. In addition, the use of some strategies such as clarifying the working processes of the clinic for staff and patients and the relationships between the clinic and other wards especially emergency department, as well as using a simple triage system on the patients’ arrival at the clinic are recommended.